Significant Efficiency Improvement Enabled by CdSe/ZnS Quantum Dot Modifier in Organic Solar Cells. Issue 8 (24th May 2019) - Wu, Lirong; Huang, Jiaming; Xie, Yangyang; Hong, Ling; Peng, Ruixiang; Song, Wei; Huang, Like; Zhu, Liqiang; Bi, Wengang; Ge, Ziyi
Abstract : Interfacial engineering plays an important role to improve the photovoltaic performance of organic solar cells (OSCs). Herein, CdSe/ZnS quantum dots (QDs) are used as a cathode interlayer (CIL) modifier. By using this strategy, an enhanced power conversion efficiency (PCE) from 13.0% to 14.6% is achieved, mainly due to the increase in open‐circuit voltage ( V oc ) and short‐circuit current density ( J sc ). A single QD layer of a proper size can reduce the defects on the surface of the active layer and smoothen the interface between the active layer and cathode. Furthermore, the low work function of the QDs with dipole moment facilitates charge transport and suppresses charge recombination at the interface by strengthening the built‐in field, thus contributing to the enhancement of PCE. The excitons generated by the QDs can also be dissociated at the IT‐4F/QD interface, which boosts the photon harvesting capability of the device. As a result, a high PCE of 14.6% is achieved for QD‐modified OSCs. Abstract : CdSe/ZnS quantum dots (QDs) are used as the cathode interlayer (CIL) modifier to enhance the power conversion efficiency of organic solar cells (OSCs) from 13.0% to 14.6% by improving the open‐circuit voltage ( V oc ) and short‐circuit current density ( J sc ). The highest reported performance in QD‐modified OSCs is achieved.